Kinetic study of seawater reverse osmosis membrane fouling - Khan, M.; De O Manes, C.; Aubry, C.; Gutierrez, L.; Croue, Jean-Philippe (2013)
Reverse osmosis (RO) membrane fouling is not a static state but a dynamic phenomenon. The investigation of fouling kinetics and dynamics of change in the composition of the foulant mass is essential to elucidate the mechanism of fouling and foulant-foulant interactions. The aim of this work was to study at a lab scale the fouling process with an emphasis on the changes in the relative composition of foulant material as a function of operating time. Fouled membrane samples were collected at 8 h, and 1, 2, and 4 weeks on a lab-scale RO unit operated in recirculation mode. Foulant characterization was performed by CLSM, AFM, ATR-FTIR, pyrolysis GC-MS, and ICP-MS techniques. Moreover, measurement of active biomass and analysis of microbial diversity were performed by ATP analysis and DNA extraction, followed by pyro-sequencing, respectively. A progressive increase in the abundance of almost all the foulant species was observed, but their relative proportion changed over the age of the fouling layer. Microbial population in all the membrane samples was dominated by specific groups/species belonging to Proteobacteria and Actinobacteria phyla; however, similar to abiotic foulant, their relative abundance also changed with the biofilm age. © 2013 American Chemical Society.